(untitled) (Journal of Information Technologies in Education (ITE), 2009)
This system would allow an easy way to bring mathematical applications to the Internet. Although the automated generation of PhP scripts is a simple task, there is no system that would allow bringing mathematical application written in any locally based system to the web. The main part of such system is simple XML-based language that fully describes source mathematical application.